SENI DAN BUDAYA DALAM PERSPEKTIF MUHAMMADIYAH - Elfan Fanhas Fatwa Khomaeny (Prodi Pendidikan Sendratasik FKIP UMTAS, 2018)
Abstract The presence of the Study Program of Drama, Dance and Music (Sendratasik) in Muhammadiyah University (PTM) becomes a challenge as well as an opportunity for the development of da'wah amar ma`ruf nahi munkar, especially the pros and cons of religious scholars (fuqahau fi diin) with artistic and cultural laws. Muhammadiyah as an Islamic movement and da'wah amar ma`ruf nahi munkar with the spirit of tajdid to carry out its movement in various aspects of human life, namely: education, health, social, economic, arts and culture, and other aspects, even KH Ahmad Dahlan as founding father using art in his dakwah. By using descriptive method, then art and culture in Muhammadiyah perspective of law is allowed, even can become fardu if in framework of da'wah amar maruf nahi munkar. As for norms and values that must be held firmly in running art and cultural activities, do not lead or cause damage (fasad), danger (dharar), iniquity (Ishyan), and distancing themselves from Allah (baid anillah).